Polyethylene glycol functionalized graphene oxide and its influences on properties of Poly(lactic acid) biohybrid materials. (15th March 2019) - Mao, Nguyen Dang; Jeong, Hun; Ngan Nguyen, Thi Kim; Loan Nguyen, Thi Mai; Vi Do, Thi Vi; Ha Thuc, Chi Nhan; Perré, Patrick; Ko, Sang Cheol; Kim, Hong Gun; Tran, Duy Thanh
Abstract: A biohybrid material based on poly(lactic acid)(PLA) incorporated with low contents of polyethylene glycol (PEG) functionalized graphene oxide (GO) was prepared via melting process and their structure, morphology, mechanical performance, and thermal properties were studied in detail. SEM and TEM characterizations confirmed that the functionalization of GO with PEG (PEGmGO) promoted its exfoliation into thin exfoliated nanosheets, thereby improving the interactions between PEGmGO filler and PLA matrix at interface. FT-IR spectra showed the presence of strong polar and hydrogen bonding interactions between components in the biohybrid. Mechanical and thermal tests indicated that there was the significant improvement of the stiffness, strength, and thermal stability of such biohybrid material with the addition of 0.3 phr PEGmGO, as compared to pure PLA, PEG-plasticized PLA, PEG-plasticized PLA/GO, and other surveyed PEG-plasticized PLA/PEGmGO biohybrids. This behavior was attributed to the homogeneous dispersion of the PEGmGO nanofillers within PLA matrix along with their strong interfacial interaction. The as-obtained biohybrids show highly potential to be useful in the bioengineering applications.